(untitled) (Olhar de Professor, 2022)
This article aims to analyze how the proposals of the National Curriculum Guidelines for the Education of Ethnic-Racial Relations and for the Teaching of Afro-Brazilian and African History and Culture are considered in the context of the Common National Curriculum Base linking Decolonial Pedagogy as a possibility for the development of an Education for Ethnic-Racial Relations that considers African and Afro-Brazilian History and Culture in the early years of Elementary School. For this purpose, the literature review was considered to subsidize propositions having as theoretical references the authors of the Modernity/Coloniality Group. Although approximations between these documents appear superficially, the possibility of working with Decolonial Pedagogy is shown as an opportunity to guarantee the right to an Education for Ethnic-Racial Relations in an Afrodiasphoric perspective.